An Exploration of Educators' Technology Integration in the Middle Grades. Issue 3 (3rd July 2021) - Kormos, Erik
Abstract: This research explored teacher in-school educational technology use for middle grades instruction. A quantitative investigation examined adoption of technology, sources of acquired skills, use frequencies, perceived effectiveness, and barriers to integration. A total of 796 participants employed across a Mid-Atlantic state from various demographic backgrounds responded to the researcher-developed questionnaire. Findings revealed document creation and presentation programs were most commonly used and perceived as the most effective tools to enhance student learning. Teachers voiced displeasure for video and audio-editing software, as well as social networking. Participants indicated personal trial and error as the most likely way to acquire new knowledge. Teacher perspectives offer unique insight and provide an opportunity to further discussion of educational technologies. By better understanding educators' use of technology in the middle grades, current teachers and administrators, as well as teacher preparation instructors, may design more reflective curricula. It is recommended that future research be performed on a multi-state or regional basis to investigate technology integration at the elementary and young adult grade levels to best prepare future teachers and keep current professionals abreast of research-based best practices.